2001
DOI: 10.1101/gad.200801
|View full text |Cite
|
Sign up to set email alerts
|

A DNA replication-arrest site RTS1 regulates imprinting by determining the direction of replication at mat1 in S. pombe

Abstract: Mating-type switching in Schizosaccharomyces pombe involves a strand-specific, alkali-labile imprint at the mat1 (mating-type) locus. The imprint is synthesized during replication in a swi1, swi3, and polymerase ␣ (swi7) dependent manner and is dependent on mat1 being replicated in a specific direction. Here we show that the direction of replication at mat1 is controlled by a cis-acting polar terminator of replication (RTS1). Two-dimensional gel analysis of replication intermediates reveals that RTS1 only term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
116
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 38 publications
2
116
0
Order By: Relevance
“…Tof1 S.c. /Swi1 S.p. is required to establish RF pausing at diverse types of endogenous RF pause sites in yeast [3][4][5][6]11 . Interestingly, however, we observed that RF pausing at Tus-Ter modules was detectable in tof1 mutants ( Supplementary Fig.…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 99%
See 2 more Smart Citations
“…Tof1 S.c. /Swi1 S.p. is required to establish RF pausing at diverse types of endogenous RF pause sites in yeast [3][4][5][6]11 . Interestingly, however, we observed that RF pausing at Tus-Ter modules was detectable in tof1 mutants ( Supplementary Fig.…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 99%
“…Two of the best examples of these in yeast are the Fob1-mediated RF pause in the rDNA array in S. cerevisiae 2 , and the RTS1 barrier at the mating type locus in S. pombe 3 . One shared feature of these programmed RF pauses is that they rely on the evolutionarily conserved intra-S-phase checkpoint mediator, Tof1 S.c. /Swi1 S.p.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, forks inevitably encounter natural replication fork barriers or termination (Ter) 2 sites in both prokaryotes and eukaryotes (3,4). Such Ter sites are usually polar or orientation-specific and, depending on the organism, presumably control proper completion of replication, chromosome segregation, recombination events, and even mating type switching in Schizosaccharomyces pombe (3)(4)(5). In Saccharomyces cerevisiae, polar fork arrest at the rDNA Ter sites presumably coordinates rDNA replication with transcription, regulates rDNA recombination, and controls the formation of extrachromosomal rDNA circles, which have been implicated in aging (6 -10).…”
mentioning
confidence: 99%
“…They have roles in a variety of tasks, including the coordination of DNA replication and transcription at eukaryotic rDNA loci (1,2), regulation of mating-type switching in yeast by strand-specific imprinting during replication (3,4), and participation in the final stages of bacterial chromosome replication and partitioning (5).…”
mentioning
confidence: 99%